2016
DOI: 10.1093/toxsci/kfw128
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Human Interindividual Variability on the Low-Dose Region of Dose-Response Curve Induced by 2,3,7,8-Tetrachlorodibenzo-p-Dioxin in Primary B Cells

Abstract: The influence of interindividual variability is not typically assessed in traditional toxicological studies. Given that chemical exposures occur in heterogeneous populations, this knowledge gap has the potential to cause undue harm within the realms of public health and industrial and municipal finances. A recent report from the National Research Council (NRC) suggests that when accounting for interindividual variation in responses, traditionally assumed nonlinear dose-response relationships (DRRs) for noncanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 40 publications
(52 reference statements)
2
23
0
Order By: Relevance
“…For instance, umbilical cord blood-derived cells were exploited to examine individual variability in the proliferative response to low-dose radiations ( 133 , 134 ). Primary human B lymphocytes from different donors were utilized to characterize the inter-individual variability in the immunotoxic effect of dioxin on the antibody secretion response and to ascertain how the variability may affect the linearization of the population-average dose response curves ( 21 ). Many of the studies with primary human cells use blood cells for their easy access; lack of easy access to solid living human tissues limits the usage of primary cells for toxicity testing.…”
Section: Computational Approaches For Dose-response and Extrapolationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, umbilical cord blood-derived cells were exploited to examine individual variability in the proliferative response to low-dose radiations ( 133 , 134 ). Primary human B lymphocytes from different donors were utilized to characterize the inter-individual variability in the immunotoxic effect of dioxin on the antibody secretion response and to ascertain how the variability may affect the linearization of the population-average dose response curves ( 21 ). Many of the studies with primary human cells use blood cells for their easy access; lack of easy access to solid living human tissues limits the usage of primary cells for toxicity testing.…”
Section: Computational Approaches For Dose-response and Extrapolationmentioning
confidence: 99%
“…Clearly some of the data gaps resulting from these challenges can be partially addressed or overcome through experimental and technological improvement, such as developing organ-on-a-chip and system-on-a-chip technology to better simulate chemical metabolism and physiological interactions, and using cells from a large number of donors to better represent human populations ( 19 21 ). However, there are fundamental limitations of the in vitro testing framework that cannot be easily improved through experimental means, and would require a computational approach to help bridge the data gaps in a feasible and cost-effective way ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, it has been developed the principle of personalized risk assessment that is referred to as the process where an individual’s level of risk is calculated using multiple predictors that are specific for an individual [ 88 ]. Such an approach is getting more and more attention as similar doses of specific xenobiotics may cause different responses not only among different species, but also among different individuals of the same species (e.g., [ 89 ]). Additionally, the presence of pathologic conditions may cause a more pronounced susceptibility making the personalized intervention even more needed for certain sub-population groups.…”
Section: In Silico Analysis In Risk Assessment: a Toxicodynamics Pmentioning
confidence: 99%
“…[13][14][15][16] In a previous study, B cells were isolated from 51 unique human donors, activated with CD40 ligand, and dosed with increasing concentrations of TCDD. 16 In comparing results across donors, profound interindividual variability was identified among the response to TCDD with up to 71-fold differences at the highest dose of TCDD (30 nM). While interindividual variability in response to toxicants can be driven by many factors, previous reports have shown that genetic background can have profound impacts on responses.…”
Section: Introductionmentioning
confidence: 99%